2017
DOI: 10.1111/dth.12465
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid in treatment of melasma: A comprehensive review of clinical studies

Abstract: Melasma is a human melanogenesis dysfunction that results in localized, chronic acquired hyperpigmentation of the skin. It has a significant impact on appearance, causing psychosocial and emotional distress, and reducing the quality of life of the affected patients. Tranexamic acid (TA) is a plasmin inhibitor used to prevent abnormal fibrinolysis to reduce blood loss and exerts its effect by reversibly blocking lysine binding sites on plasminogen molecules, thus inhibiting plasminogen activator (PA) from conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 35 publications
0
72
0
5
Order By: Relevance
“…Several studies have demonstrated the efficacy of TA in treatment of melasma [411], but in a large number of these studies, TA have been used orally with numerous systemic side effects such as menstrual irregularities, gastrointestinal symptoms, and orthostatic imbalances [1315]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the efficacy of TA in treatment of melasma [411], but in a large number of these studies, TA have been used orally with numerous systemic side effects such as menstrual irregularities, gastrointestinal symptoms, and orthostatic imbalances [1315]. …”
Section: Discussionmentioning
confidence: 99%
“…Tranexamic acid (TA), an inhibitor of plasminogen activation, has been recently used in the treatment of melasma in different investigations [411]. The exact mechanism of action of tranexamic acid is still unknown, but the evidence shows that it can reduce the melanin content of epidermis, decrease the dermal vascularity, and mast cell numbers[7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TA has a similar structure to tyrosine and may competitively inhibit the tyrosinase enzyme, thus also decreasing melanin synthesis through this mechanism. Furthermore, it is hypothesized that TA may reduce the vascularity of hyperpigmented areas by blocking vascular endothelial growth factor and endothelin‐1 …”
Section: Systemic Therapies For Skin Lighteningmentioning
confidence: 99%
“…Before starting systemic TA treatment, patients should be thoroughly screened for any personal or familial history of coagulation disorders as well as risk factors for clotting such as use of birth control pills, pregnancy, and smoking. The most common reported adverse events include gastrointestinal distress, headaches, rash, and menstrual irregularities . In a study of 561 patients, 1 patient developed deep vein thrombosis while on oral TA treatment for melasma.…”
Section: Systemic Therapies For Skin Lighteningmentioning
confidence: 99%
“…A 12‐week comparative study of intradermal microinjections of TA (4 mg/mL every 4 weeks; n = 50) vs. oral TA (250 mg twice daily; n = 50) suggested that both routes of administration could elicit comparable reductions in MASI . A subsequent review of all reported studies of TA for treatment of melasma identified only one study (of six) supporting the use of topical TA, and suggested that while intradermal TA injections may be helpful, the largest series required weekly injections for 12 weeks, which may limit its use for busy patients and clinicians.…”
mentioning
confidence: 99%